THE ROLE OF COURSE INSTITUTIONS IN EMPOWERING "KAMPUNG INGGRIS" VILLAGES THROUGH SERVICES BUSINESS - Rozi, Muhamad Fahrur; Sunarti, Vevi; Dwi Arini, Fitri; Husnul Hayati, Ridha; Septia Landa, Klara (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This study intends to describe the function of the course institutions in empowering communities via roadster bicycle rental services. This study employs a qualitative research method based on case studies. This study utilized in-depth interviews, observation, and documentation studies to collect data. Techniques for data analysis consist of the steps of data management, data description, data classifications, data interpretation, data presentation, and conclusion drawing. Triangulation of the source method and triangulation of approaches are utilized in the process of validating the findings. The results of the study indicate that the course institutions play a crucial role in enhancing the local economy. Student mobility during taking the course in "Kampung Inggris" was high enough that the local community can be used to create economic opportunities. Economic opportunities are created by providing students with teaching courses with roadster bicycle rental services. The potential to boost the economy was utilized by a population for the first time in 1998. Since then, hundreds of roadster bicycle rental services have been formed, and some of them have even become family businesses in Tulungrejo village. Improving the economics of the Tulungrejo village community is inextricable from the role of the Mahesa Institute, which promotes the use of bicycles for student mobility during the "English Village" course.